2013
DOI: 10.17532/jhsci.2013.111
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of joined disabilities of children with cerebral palsy in Tuzla canton

Abstract: Introduction: Cerebral palsy (CP) connotes a group of non-progressive, but often variable symptoms of motor impairment of movement and posture, as well as other impairments which are a consequenceof anomalies or brain impairment in different phases of its development. CP is a pathological condition characterised in the fi rst place by motor function impairment to which other disorders such as: visual andhearing impairment, intellectual defi cit, emotional problems, behaviour disorder, speech disorder, epilepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Basic statistical parameters of frequency and percentages were calculated, and tabular presentation was made. After classification of examinees as per frequency of joined disabilities was done, work results have shown that speech impairment occurred with 35.4 % of children, visual impairment 33.3 %, epilepsy 29.3 %, whereas hearing impairment occurred with 2 % of children (Babajić M, Švraka E, Avdić D, 2013).…”
mentioning
confidence: 99%
“…Basic statistical parameters of frequency and percentages were calculated, and tabular presentation was made. After classification of examinees as per frequency of joined disabilities was done, work results have shown that speech impairment occurred with 35.4 % of children, visual impairment 33.3 %, epilepsy 29.3 %, whereas hearing impairment occurred with 2 % of children (Babajić M, Švraka E, Avdić D, 2013).…”
mentioning
confidence: 99%